Patients With Low Drug Levels or Antibodies to a Prior Anti–Tumor Necrosis Factor Are More Likely to Develop Antibodies to a Subsequent Anti–Tumor Necrosis Factor - Vande Casteele, Niels; Abreu, Maria T.; Flier, Sarah; Papamichael, Konstantinos; Rieder, Florian; Silverberg, Mark S.; Khanna, Reena; Okada, Lauren; Yang, Lei; Jain, Anjali; Cheifetz, Adam S. (Clinical gastroenterology and hepatology, 2022)
Therapeutic drug monitoring (TDM) with measurement of serum drug and antidrug antibodies (ADAb) is used widely to confirm therapeutic exposure, rule out immunogenicity, and optimize treatment of biologics in patients with inflammatory bowel diseases.1 A recent genome-wide association study found the variant HLA-DQA1∗05 to increase the risk of development of antibodies against infliximab (IFX) and adalimumab (ADM) 2-fold, regardless of concomitant immunomodulator use.2,3 However, there is currently limited evidence showing whether patients who develop antibodies to 1 anti–tumor necrosis factor (TNF) are prone to develop antibodies to the subsequent anti-TNF. Our aim was to investigate the risk of subsequent antibody development in cases (with ADAb to prior anti-TNF) versus control subjects (without ADAb to prior anti-TNF) using a large cohort of patients with inflammatory bowel diseases who underwent TDM with a drug-tolerant assay.